CHARITY IN THE SYSTEM OF EUROPEAN PRINCIPLES: EXPERIENCE FOR UKRAINE - Корнієвський, О.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article analyzes some aspects of the European charity traditions, their influence on the formation and the development of modern European philanthropy. Special attention is paid to the analysis of the phenomenon of charity as an essential component of the modern welfare-oriented state. It is proved that the level of population’s involvement to charity activities depends on the level of the development of civil society in general.